Evaluating the fermentation characteristics, bacterial community, and predicted functional profiles of native grass ensiled with different additives - Du, Shuai; You, Sihan; Jiang, Xiaowei; Li, Yuyu; Wang, Ruifeng; Ge, Gentu; Jia, Yushan (Frontiers in Microbiology, 2022)
Bioaugmentation of native grass ensiling with Lactobacillus plantarum or Lactobacillus buchneri or Pediococcus pentosaceus on the ensiling performance and bacterial community was investigated. The native grass inoculated with distilled water, Lactobacillus plantarum, Lactobacillus plantarum and Lactobacillus buchneri, and Lactobacillus plantarum, Lactobacillus buchneri and Pediococcus pentosaceus as the CON group, T1 group, T2 group and T3 groups, respectively. The addition of lactic acid bacteria was at 1 × 106 colony-forming unit/g fresh matter. As expected, the markedly (p < 0.05) lower WSC content was tested in the T2 and T3 groups compared to the CON and T1 groups. Compared to the CON and T1 groups, the significantly (p < 0.05) higher crude protein content, and lower acid detergent fiber and neutral detergent fiber contents were found the T2 and T3 groups. Compared to the CON group, the pH was decreased in the LAB inoculated silage, and the lowest pH was measured in the T3 group. Similarly, the significantly higher lactic acid and acetic acid contents were also found in the T3 group compared to those in other groups. After 30 days of ensiling, the Shannon and Chao1 in silages were decreased compared to that in the fresh materials (FM). The principal coordinates analysis indicates that both fresh native grass and silage were separately in each group with no interactions on the confidence ellipse (R = 0.8933, p = 0.001). At the phylum level, the dominant phylum was shifted from Proteobacteria to Firmicutes after fermentation process. Interestingly, Weissella dominated the fermentation in the CON group and Lactobacillus dominated the fermentation in all inoculated LAB silage at the genus level. Results of functional prediction analyses showed that the metabolism of carbohydrate metabolism were significantly reduced after ensiling. The complex LAB (Lactobacillus plantarum, Lactobacillus buchneri and Pediococcus pentosaceus) exhibited the potential possibility to decrease pH and enhance the relative abundance of LAB in response to get high-quality silage by the priority effects. These results suggested that the complex LAB could improve the ensiling performance of native grass silage, lay a theoretical basis for inoculant application in native grass.